Reconstructing Teacher Identity in the AI Era: A Qualitative Study of EFL Teachers in a Chinese Private College - Jiang, Weiwei (Journal of Social Science and Humanities, 2025)
This study explores the professional identity reconstruction of English as a Foreign Language (EFL) teachers amid the integration of artificial intelligence (AI) into education. Using a qualitative multiple-case design, four English teachers from a Chinese private college participated in semi-structured interviews. Data were thematically analyzed, and four core dimensions were identified: (1) duality of teachers’ emotional experiences in AI integration; (2) diverse pathways of identity reconstruction; (3) multi-level interactive influences; and (4) ethical considerations in identity reconstruction. Based on the findings, the study highlights the need for comprehensive support systems covering technical training, psychological support, ethical guidance, and institutional backing. These insights help with discussions about EFL teacher development. They also help create educational policies that support AI use in English teaching.